Assessment of Nurses’ Knowledge of Multiple Sclerosis in Morocco - Rachid Lotfi; Hind Bel Amgharia; Mourad Chikhaoui; Abdeslam El Kardoudi; Fatiha Chigr (Fakultas Ilmu Keperawatan Universitas Indonesia, 2025)
Nurses are essential in early detection, education, symptom management, treatment administration, and care coordination for patients with multiple sclerosis (MS). This role requires both theoretical and practical knowledge. This study evaluates the knowledge level among nurses regarding multiple sclerosis in Morocco. We conducted this cross-sectional study on 326 nurses in Morocco using a purposive sampling method, which involves selecting nursing specialties that have direct contact with patients with MS, aiming to target the most relevant professionals for the study. The data are collected using an anonymous questionnaire distributed individually to participants. We opted for multivariable logistic regression models to analyze the data. The results highlighted a significant deficit in nurses’ knowledge of MS. Only 28.8% recognized it as a chronic disease, while nearly half identified it as autoimmune, inflammatory, or neurodegenerative. Commonly reported symptoms included sphincter abnormalities (56.4%), visual disorders (44%), spasticity (27.6%), sexual problems (26%), and cognitive issues (23.9%). Concerning risk factors, 46% attributed MS primarily to genetics, while 40% were unaware of any factors. Nearly half (47%) believed MS therapy is symptomatic, and only 33% were familiar with disease-modifying therapies (DMTs). 90% of nurses lacked continuous MS training. The study found significant associations between nurses’ knowledge and variables such as department of work (p = 0.045), gender (p = 0.041), and profile (p = 0.039). Lack of knowledge about MS may negatively influence early diagnosis and management of MS. To address this issue, we recommend improving the foundational training of healthcare professionals and introducing continuous education programs. Keywords: knowledge, Morocco, multiple sclerosis, nurse Abstrak Menilai Pengetahuan Perawat tentang Multiple Sclerosis di Maroko. Perawat berperan penting dalam deteksi dini, pendidikan, manajemen gejala, pemberian pengobatan, dan koordinasi perawatan untuk pasien dengan multiple sclerosis (MS). Peran ini membutuhkan pengetahuan teoritis dan praktis. Penelitian ini menilai pengetahuan perawat tentang MS di Maroko. Kami melakukan studi cross-sectional ini pada 326 perawat di Maroko dengan menggunakan metode purposive sampling, yang melibatkan pemilihan spesialisasi keperawatan yang kemungkinan memiliki kontak langsung dengan pasien MS, dengan tujuan untuk menargetkan profesional yang paling relevan untuk penelitian ini. Data dikumpulkan dengan menggunakan kuesioner anonim yang didistribusikan secara individual kepada peserta. Kami memilih model regresi logistik multivariabel untuk menganalisis data. Penelitian ini menyoroti kekurangan yang signifikan dalam pengetahuan perawat tentang MS. Hanya 28,8% yang mengenali MS sebagai penyakit kronis, sementara hampir separuhnya mengidentifikasinya sebagai autoimun, inflamasi, atau neurodegeneratif. Gejala yang umum dilaporkan termasuk kelainan sfingter (56,4%), gangguan penglihatan (44%), spastisitas (27,6%), masalah seksual (26%), dan gangguan kognitif (23,9%). Mengenai faktor risiko, 46% mengaitkan MS terutama dengan faktor genetik, sementara 40% tidak mengetahui faktor apapun. Hampir setengah (47%) meyakini terapi MS bersifat simtomatik, dan hanya 33% yang akrab dengan disease-modifying therapies (DMT). Lebih jauh lagi, 90% perawat tidak memiliki pelatihan MS berkelanjutan. Penelitian ini menemukan hubungan yang signifikan antara pengetahuan perawat dan variabel seperti departemen kerja (p = 0,045), jenis kelamin (p = 0,041), dan profil (p = 0,039). Kurangnya pengetahuan tentang MS dapat berdampak negatif pada diagnosis dini dan manajemen penyakit ini. Untuk mengatasi masalah ini, kami merekomendasikan untuk meningkatkan pelatihan dasar bagi para profesional kesehatan dan memperkenalkan program pendidikan berkelanjutan. Kata Kunci: Maroko, multiple sclerosis, pengetahuan, perawat